Transformation of Ijtihad of Nusantara Ulama in the Formulation of A Compilation of Sharia Economic Law from A Maslahah Perspective - Arifin, Zarul; Neli, Neli; Abdussalam, Izuddin; Yacob, Fakhri (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study discusses the transformation of ijtihad of Indonesian scholars in the formulation of the Compilation of Sharia Economic Law (KHES) using the maslahah perspective as the basis of analysis. KHES is the result of the codification of Islamic economic law in Indonesia that seeks to address the dynamics of the modern economy through a contextual approach to classical Islamic legal sources. Indonesian scholars have an important role in the ijtihad process by adapting sharia values to align with the social, cultural, and economic realities of Indonesian society. Through the maslahah mursalah approach, the transformation of ijtihad not only maintains the principles of justice and maslahah, but also reflects the flexibility of Islamic law in responding to developments in the era. This study found that KHES is the result of synergy between classical fiqh texts and the needs of contemporary economic practice, where maslahah becomes the main instrument to maintain the relevance and acceptability of Islamic law in the national economic realm. Thus, KHES reflects a concrete form of moderate, contextual, and oriented Nusantara Islam to the welfare of the people in the economic field.